False-positive cardiac troponin I values due to macrotroponin in healthy athletes after COVID-19 - Hammerer-Lercher, Angelika; Kissel, Christine K.; Wittfooth, Saara; Junes, Helea; Kaplan, Emel; Huré, Gabrielle; Sanzone, Alessandra; Neyer, Peter; Bernasconi, Luca; Manka, Robert; Noack, Patrik; Hof, Daniëlle; et al. (Walter de Gruyter GmbH, 2026)
Objectives
Cardiac troponins (cTn) are used to detect and quantify acute cardiomyocyte injury. In patients presenting with symptoms that could indicate myocarditis, elevated cTn concentrations typically mandate cardiac catheterization and heart muscle biopsy or cardiac magnetic resonance imaging (CMR). Accordingly, increased cTn levels due to macrotroponin – a complex between patient anti-troponin autoantibodies and cTn – could lead to unnecessary and potentially harmful interventions. In athletes, ensuring cardiac health after infection like COVID-19 is critical, but the occurrence of false-positive cTn levels post-COVID-19 remains unknown.
Methods
This observational study prospectively included 35 healthy athletes (aged 16–75 years; 19 females, 16 males) who underwent post-COVID check-ups during 2022–2023. Athletes’ cTn levels were measured using four different hs-cTn routine immunoassays. If discrepancies were noted between assays, further testing for macrotroponin was conducted using protein G column, sucrose gradient ultracentrifugation and anti-troponin autoantibody immunoassay.
Results
Seventeen athletes had normal cTn levels across all assays, while 18 (51 %) had elevated cTn, mostly cTnI. Despite elevated cTn levels, no signs of myocarditis or other cardiac conditions were found on electrocardiography, echocardiography, or CMR. Macrotroponin was confirmed among 16 of these 18 athletes. Further, IgG anti-troponin autoantibodies correlated significantly with the levels of the two most-commonly affected assays: hs-cTnI-Siemens Atellica and hs-cTnI-Abbott Alinity.
Conclusions
Post-COVID-19, nearly half of athletes showed elevated cTnI levels due to interference from macrotroponin. Awareness among physicians and laboratorians of this analytical confounder can avoid unnecessary invasive or costly diagnostic tests in athletes with false-positive cTnI levels after COVID-19.